Las dificultades de aprendizaje en el área de lengua y literatura y su relación con el proceso lectoescritor de las niñas y niños de quinto, sexto y séptimo grados del subnivel básica media, de educación general básica, de la escuela de educación básica “Luis Antonio Erique Ortega”, barrio El Plateado, parroquia Sucre, de la ciudad de Loja. Año lectivo 2012-2013 - Quezada Paredes, Sandra del Rocío (2014)
In this investigative work the conceptual foundations are analyzed about learning disabilities, where is offered a view of the current state of this issue, what is your relationship with the different areas of knowledge and how are they presented in the evolutionary development of each individual, reason for which has been called for the current work of search: "LEARNING DIFFICULTIES IN THE AREA OF LANGUAGE AND LITERATURE AND ITS RELATIONSHIP WITH THE PROCESS LECTOESCRITOR FOR GIRLS AND BOYS FIFTH, SIXTH, AND SEVENTH DEGREES OF THE SUBLEVEL BASIC AVERAGE OF BASIC GENERAL EDUCATION, BASIC EDUCATION SCHOOL “LUIS ANTONIO ERIQUE ORTEGA” THE SILVER DISTRICT, PARISH SUCRE FROM THE CITY OF LOJA, 2012-2013 ACADEMIC PERIOD. This work provides an overview of the relationship that exists between the proposed variables and know the reality at this stage of the inquiry. This topic has been researched by become a prevailing necessity in the field of education and that negatively affects the daily life of the children of the aforementioned educational institution, problems that significantly limit their lectoescritor process. And relation to the theoretical part, are common problems in educational institutions, which include spelling flaws, limited vocabulary, and the most significant difficulties related to literacy. It is worth mentioning that she worked with a population of 150 students, 6 teachers and a principal; this research was carried out using framed within qualitative research methodological processes, the techniques and instruments used include the personalized interview lady principal and teachers of the above-mentioned educational institution and the application of questionnaires to children in grades that the proposal itself will work, giving as a result of the investigation, confirmation of the assumptions made, corroborating it as well, the existence of the problem, in the same way are encouraged to the teaching staff and managers to continue to work in that spirit humanist that characterizes them, so lojana childhood educating on this campus will give fruits of noble work, which is teaching.